The role of C/EBPbeta in regulating UCP1 expressions in 3T3-L1 adipocytes - Liu, Qian (2012)
Uncoupling protein 1 (UCP1) is essential for non-shivering thermogenesis in brown adipose tissue (BAT) by dissipating proton-motive force to stimulate maximum mitochondrial respiration. cAMP-dependent protein kinase induction of UCP1, as well as the PPAR coactivator1α (PGC1α), is a typical characteristic in BAT but not in white adipose tissue (WAT). Previous work demonstrated that the overexpression of CCAAT/Enhancer Binding Protein β (C/EBPβ) could rescue the cAMP-induced PGC1α and UCP1 expression in white preadipocytes 3T3-L1 cell line, indicating a key regulatory role of C/EBPβ in brown adipogenesis. The overall aim of this study was to examine the role of C/EBPβ overexpression in regulating the transcription of UCP1 in 3T3-L1 white preadipocytes to transform them to a more brown-like cell phenotype.